Analisis Kepatuhan Pengobatan Diabetes Melitus (DM) Pada Peserta Prolanis Di Wilayah Kerja Puskesmas Selindung Kota Pangkalpinang Tahun 2026 - Nelly Bastina; Dedek Sutinbuk; Taufik Kurrohman; Heru Listiono; Ferly Oktriyedi (Jurnal Ners, 2026)
Diabetes mellitus (DM) is a chronic disease with an increasing prevalence and requires treatment adherence to prevent complications. Low treatment adherence among participants of the Chronic Disease Management Program (PROLANIS) remains a problem at Selindung Public Health Center, Pangkalpinang City. This study aimed to analyze medication adherence and its associated factors among PROLANIS participants with DM in the working area of Selindung Public Health Center in 2026. This study used a quantitative design with a cross-sectional approach. The sample consisted of PROLANIS participants with DM selected using total sampling technique. Data were analyzed using univariate analysis, bivariate analysis with chi-square test, and multivariate analysis with logistic regression. The results showed that most respondents were non-adherent to DM treatment. There were significant relationships between age, gender, education level, occupation, duration of DM, knowledge, family support, and health workers’ support with medication adherence (p<0.05). Knowledge was identified as the most dominant factor associated with medication adherence. This study concludes that improving patient knowledge, family support, and support from health workers play important roles in enhancing medication adherence among PROLANIS participants with DM. Keywords: Diabetes Mellitus, Medication Adherence, PROLANIS, Knowledge, Family Support